THE ROLE OF ISLAMIC FINANCIAL LITERACY FROM THE PERSPECTIVE OF MAQASID AL-SHARIAH: A CASE STUDY OF COMMUNITY OF NAKA IN KEDAH (International Journal of Islamic Business, 2024)
The research highlights a limited understanding of Maqasid al-Shariah and financial management principles among the rural community, coupled with inadequate digital and financial literacy. Economic hardships, lack of access to modern financial tools, and insufficient emphasis on long-term planning hinder their ability to achieve financial stability and align their practices with Islamic financial goals. Islamic financial literacy, when viewed through the lens of Maqasid al-Shariah, offers a holistic and ethical approach to financial management that aligns with the core objectives of Islamic law. Maqasid al-Shariah, aim to promote the welfare of individuals and society by preserving religion, life, intellect, progeny, and wealth. This study examines how these objectives shape financial literacy within an Islamic framework, emphasizing principles such as the prohibition of Riba (interest), the importance of Zakat (charitable giving), ethical investment, and the avoidance of extravagance and waste. The research employs a qualitative approach, utilizing secondary data collection through desktop research to analyze existing literature on Islamic financial literacy from the perspective of Maqasid al-Shariah. Additionally, it incorporates findings from a case study conducted in Naka, Kedah, focusing on the financial literacy and Islamic financial practices of villagers, supported by a pilot test with 27 participants who responded to workshop-survey sessions. By promoting a balanced and just approach to wealth management, Islamic financial literacy guided by Maqasid al-Shariah aims to advance financial stability, social equity, and overall well-being, thereby contributing to the holistic development of both individuals and communities. This research contributes by integrating Islamic financial literacy with Maqasid al-Shariah, offering a holistic framework for ethical financial management that promotes social welfare, enhances financial stability, and provides practical insights for empowering underserved communities through targeted education and tools aligned with Islamic principles.